Allyl Complexes of Tungsten from the Rearrangement of Transient Cyclopropyl Precursors. Issue 42 (26th September 2019) - Parker, Kyle D. J.; Labat, Stéphane; Sotiropoulos, Jean‐Marc; Miqueu, Karinne; Pimienta, Véronique; Vendier, Laure; Etienne, Michel
Abstract : This article explores the contrasting reactivity of cyclopropyl complexes of early transition metals. [Cp*W(NO)(CH2 R)( c ‐C3 H5 )] (R = SiMe3, Ph, t ‐Bu) generated in THF solution from [Cp*W(NO)(CH2 R)Cl] and [Mg( c ‐C3 H5 )2 (dioxane)x ] readily rearrange to η 3 ‐allyl derivatives [Cp*W(NO)(CH2 R)(η 3 ‐C3 H5 )] by an intramolecular ring opening reaction. Both direct and catalyzed pathways are revealed by kinetic studies. Computational modeling indicates the ring opening reaction is preferred on thermodynamic grounds for tungsten whereas kinetic products arising from β‐H abstraction reactions of cyclopropane are observed for related zirconium and niobium complexes reported previously. The energetic accessibility and the nature of the LUMO in the tungsten complexes promote distal CC bond cleavage in the cyclopropyl ring. Abstract : In situ generated alkyl cyclopropyl complexes of tungsten readily rearrange to η 3 ‐allyl complexes thanks to an easily accessible LUMO which favors distal CC bond cleavage in contrast to cyclopropane elimination observed for zirconium and niobium analogues.